La Didáctica para la Comprensión Lectora en los niños de tercer año de Educación Básica de la Escuela de Educación Básica Capullitos - Garcés Rocha, María Fernanda (2021)
The objective of this research was to establish the didactic process in reading comprehension, which is developed in the third grade of elementary school at “Capullitos” educational unit in Riobamba city, analyzing each stage, identifying the weaknesses and strengths for taking decisions to support an adequate academic development. It presents a mixed approach, since data was collected systematized in numerical and percentage tables, which were analyzed qualitatively to describe the problems found; it is non-experimental, since the studied population was not manipulated. It a descriptive type, because it details the elements about the identification problem this has not been studied in the selected field. A field type since the data was collected directly at the scene of the investigation, during the first quarter of the 2020-2021 school year. Correlational level since it aims to relate the didactic fact with its impact on the maturation of skills related to reading comprehension. The research was carried out in the city of Riobamba, La Lizarzaburu parish, urban sector. The population was 25 children enrolled in the third year of elementary school and two tutors from parallels A and B. Among the findings, the most relevant is the fact that the stages of paratexts work in children are not mature in the different percentages, the ability to return to the text, find information in the reading, but above all the greatest weakness is the paraphrasing. Among the data related to teachers, the weakness found is that 50% of teachers do not carry out activities related to the development of paraphrasing in third grade children. It is concluded that students need to be strengthened in the stages of reading comprehension so that the weak percentages acquire these skills and do not advance to the next educational level with deficiencies. Teachers' training or study circles are imperative. to diversify the didactic strategies of reading comprehension.